1996
DOI: 10.1016/0014-5793(96)01118-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerase I changes the mode of interaction between camptothecin drugs and DNA as probed by UV‐resonance Raman spectroscopy

Abstract: Pronounced differences of interactions of camptothecin (CPT) and its derivative 7-ethyl-10-[4-(1-piperidino)-lpiperidino]carbonyloxycamptothecin (CPTll), inhibitors of DNA topoisomerase I, with oligonucleotides were found using UV resonance Raman spectroscopy. 30-mer oligonucleotides were derived from the sequences of the topoisomerase I-induced and CPT-enhanced cleavage sites in SV40 DNA. CPT induces well-defined alterations of the oligo structure, whereas CPTll interacts with oligonucleotides more weakly and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…UV resonance Raman wavenumbers (cm À1 ) and tentative assignments of LacDNA complexes in different physico-chemical conditions, of the corresponding single-stranded oligonucleotides and of the proper sum of spectra of single oligonucleotides. [1,5,11,19,20,[23][24][25][26][27][28][29][30][31][32] Raman spectra were excited with a 275 nm laser line. The spectral resolution was appreciated to be 3 cm Intensity changes can also give insight into changes in coupling or electronic structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…UV resonance Raman wavenumbers (cm À1 ) and tentative assignments of LacDNA complexes in different physico-chemical conditions, of the corresponding single-stranded oligonucleotides and of the proper sum of spectra of single oligonucleotides. [1,5,11,19,20,[23][24][25][26][27][28][29][30][31][32] Raman spectra were excited with a 275 nm laser line. The spectral resolution was appreciated to be 3 cm Intensity changes can also give insight into changes in coupling or electronic structure.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, dA and dG residues were also found to contribute to this band. [23,26,27,32] Very informative is the guanine band at 1490 cm À1 , which decreases in intensity upon binding of electrophilic agents to the N7 acceptor of guanine. [1,19,23] This vibration is known to be very sensitive to any ligation or complexation involving the N7 ([Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that inhibitors of topoisomerase strongly suppress SV40 DNA replication , suggesting that topoisomerase I is required for efficient SV40 replication. CPT reportedly induces remarkable alternations of oligonucleotides containing the sequences of the topoisomerase I‐induced and CPT‐enhanced cleavage sites in SV40 DNA, whereas CPT11 interacts more weakly and in a different manner than CPT . It is possible that CPT11 forms a ternary complex with topoisomerase I and JCPyV DNA by binding reversibly at DNA cleavage sites.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treatment with topotecan or β‐lapachone results in marginal inhibition of viral propagation in JCI cells, which produce high titers of JCPyV, according to RT‐PCR analysis . In contrast, UV resonance Raman spectroscopy using oligonucleotides derived from the sequences of topoisomerase I‐induced and CPT‐enhanced cleavage sites in SV40 DNA showed differences in the interactions of CPT and CPT11 . This report led us to seek other topoisomerase inhibitors of JCPyV, a synthesized CPT derivative that has been shown to be associated with inhibition of topoisomerase I.…”
mentioning
confidence: 99%